Is The Technology Acceptance Model Valid For Entrepreneurs? Model Testing And Examining Usage Determinants - Oly Ndubisi, Nelson; Muhamad Jantan, Muhamad Jantan; Richardson, Stanley (Asian Academy of Management (AAM), 2001)
IT researchers regard Technolog}' Acceptance model (TAM) as a powerful model for understanding technology acceptance in general. Many have claimed it is the most popular model of technology acceptance, having been used in many studies involving different user groups. But very often overlooked is the test of TAM on entrepreneurs, a distinct and important group which researchers have found to exhibit unique traits. Because of these peculiar traits, this research believes that a separate TAM study on entrepreneurs is warranted. TAM theorizes that perceived usefulness directly influences usage and perceived ease of use directly and indirectly via usefulness influences usage. This research investigates the validity of the TAM among Malaysian entrepreneurs.This is because because TAM has not been examined across cultures like Malaysia with a multi-racial and fast developing economy. The study found that IT usage was influenced directly by perceived usefulness and indirectly (via usefulness) by perceived ease of use. Contrary7 to TAM’s postulation, there is no direct relationship between perceived ease of use and usage. Details of the research findings and their implications are discussed